Antibiotic governance and use on commercial and smallholder farms in eastern China - Liu, Binjuan; Wang, Wei; Deng, Ziru; Ma, Cong; Wang, Na; Fu, Chaowei; Lambert, Helen; Yan, Fei (Frontiers in Veterinary Science, 2023)
China is one of the largest consumers of agricultural antibiotics in the world. While the Chinese government has been tightening its regulations to control antimicrobial resistance (AMR) from animal sources in recent years, the extent of antimicrobial oversight and the practices of antibiotic use in animal agriculture in China has not yet been explored. Drawing on 33 interviews with government agriculture officials, veterinary drug sellers, farmers and smallholders, this study describes the practices of antimicrobial management in eastern China and current scenarios of antibiotic use in commercial farms and smallholder backyard farming. Findings revealed that although the governance of antibiotic use has made progress, especially in controlling irrational antibiotic use in commercial farms, smallholders are under-regulated due to a lack of resources and assumptions about their marginal role as food safety governance targets. We also found that smallholders resort to human antibiotics for the treatment of backyard animals because of economic constraints and lack of access to professional veterinary services. More attention needs to be devoted to the local structural needs of farmers to reduce antibiotic misuse. Considering the extensive links of AMR exposure under the One Health framework, efforts to integrate smallholders in antibiotic governance are required to address AMR burden systematically in China.